Rancang Bangun Kompor Biomassa Otomatis Berbasis Sensor Suhu dan Mikrokontroler - Mareli Telaumbanua; Ahmad Ridho Kurniawan; Agus Haryanto; Raizummi Fil’aini; Febryan Kusuma Wisnu; Winda Rahmawati (Jurnal Ilmiah Rekayasa Pertanian dan Biosistem, 2025)
Continuous consumption of fossil fuels can cause fuel prices to rise and potentially cause shortages. One alternative renewable energy that can replace fossil fuels is biomass pellets. The use of manual biomass pellet stoves has constraints in controlling the amount of biomass burned, the amount of heat released by the stove, combustion efficiency, safety, and wasteful use of pellets. The purpose of this study was to develop a biomass stove using an automatic control system as a substitute for gas or electric stoves. This stove has the same principle and working method as gas stoves in general, but the pellet fuel is solid. This technology controls the temperature through the integration of temperature sensors, fan blowers, screw feeders, and heat insulators automatically. The results showed that the stove temperature value with the coefficient of determination value from sensor calibration 1 was R2 = 0.9945, sensor calibration 2 obtained the value R2 = 0.9956, the R2 value in sensor calibration 3 was 0.9946, and sensor calibration 4 obtained the value R2 = 0.9927. In the system response test, the device was able to reach a temperature of 300°C in 450 to 780 seconds. Stability testing for setting points 100°C, 200°C, and 300°C were 0.98, 0.82, and 0.53, respectively. The accuracy of the device was 92%. In the execution speed test, it took 2.5 to 4 seconds for the pellets to enter the fuel furnace.